Potential materials for teaching akhlak tasawuf based on West Kalimantan's local wisdoms - Elmansyah, Elmansyah (ATTARBIYAH: Journal of Islamic Culture and Education, 2024)
This research aims to reveal various potential teaching materials for Sufism Morals courses that are available, and are original from the West Kalimantan region. This is important, in order to provide a more comprehensive picture of Sufism in the West Kalimantan region, such as the typology, characteristics, personalities and teachings that are exclusive to Sufism figures. The method used in this study is qualitative with a philological hermeneutic approach. Based on the results of philological analysis of classical books found by researchers, the following conclusions are obtained: Firstly, in West Kalimantan, as well as known that many books of Sufism founded, i.e., The Book of Nashihat Zaman the work of Sharif Shaleeh al-Idrus; The Book of Syarah al-Hikam written by Sheikh Muhammad As'ad Selakau; The Manuscript of Hajj Abdul Malik Krui; The Book of Zikir Tauhidiyah by Syeikh Ismail Mundu, etc. Secondly, these books show that since a long time ago the Sufism was established in West Kalimantan. Thirdly, the result from a parallel content analysis indicated that the Sufism course's teaching material had not raised a lot of local knowledge only, but the potential material show from various aspects, i.e., the History of Sufism, the figure of Sufis, moral teachings, and Sufism manuscripts.